2022
DOI: 10.1007/s12350-021-02612-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of incidental right ventricular abnormalities identified on SPECT for mortality and pulmonary hypertension

Abstract: Background. The clinical significance of incidentally found RV abnormalities on low-risk SPECT studies is not well-defined. The objective of this study was to determine the predictive value of incidental right ventricular (RV) abnormalities identified on single photon emission computed tomography (SPECT) scans for mortality and pulmonary hypertension (PH).Methods. We retrospectively analyzed all low-risk SPECT studies in patients without known coronary artery or pulmonary vascular disease, performed at our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…5,12 Jose et al suggest that incidental RV abnormalities found on low-risk MPS are significantly and independently associated with increased mortality and could identify high-risk patients for closer monitoring and additional diagnostic testing. 25 Brunken further suggests that a structured nuclear cardiology report would benefit from the inclusion of information about RV volumes, RVEFs, and global and regional RV function for each SPECT perfusion study. 26 Accordingly, our proposed method has important clinical values for the research and development of RV functional assessment on MPS.…”
Section: Clinical Values Of Rv Segmentation and Functional Assessmentmentioning
confidence: 99%
“…5,12 Jose et al suggest that incidental RV abnormalities found on low-risk MPS are significantly and independently associated with increased mortality and could identify high-risk patients for closer monitoring and additional diagnostic testing. 25 Brunken further suggests that a structured nuclear cardiology report would benefit from the inclusion of information about RV volumes, RVEFs, and global and regional RV function for each SPECT perfusion study. 26 Accordingly, our proposed method has important clinical values for the research and development of RV functional assessment on MPS.…”
Section: Clinical Values Of Rv Segmentation and Functional Assessmentmentioning
confidence: 99%
“…Accordingly, Jose and colleagues sought to examine the ramifications of an abnormal RV on low-risk SPECT perfusion studies acquired over a thirteen-year period at the University of Cincinnati. 9 STUDY DESIGN They reviewed 12,883 SPECT perfusion records and identified 4,761 exams with normal LV perfusion. None of the study patients had heart failure, PH, prior MI or valvular disease, and none demonstrated transient LV dilatation with stress.…”
mentioning
confidence: 99%